Phytoseiid Mites (Parasitiformes, Phytoseiidae) of Lesvos Island (Greece) with a Description of a New Species - Ragusa, S.; Tsolakis, H. (ENTOMOLOGIA HELLENICA, 1998)
A survey of phytoseiid mites associated with crops and wild plants on Lesvos Island was conducted. Of twenty three species collected the most abundant were the following: Phytoseius finitimus Ribaga sensu Denmark (30%), Euseius finlandicus (Oudemans) and Typhlodromus psyllakisi Swirski and Ragusa (26%), Typhlodromus athenas Swirski and Ragusa (19%), Typhlodromus cryptus Athias-Henriot, and Typhlodromus intercalaris Livshitz and Kuznetsov (15%). A new species, Typhlodromus sapphicus sp. n., collected on Tilia sp. is also described.